Activated carbons developed in different activation conditions to improve nitrate adsorption performance - Roman, S. (2016)
The suitability of activated carbons (ACs)with dissimilar textural and surface chemistry characteristics was studied for nitrate removal, under different pH conditions. For this task, four ACs were used; two of them were manufactured bychemical and physical steam activation from orange peel and almond shell, while the other two were commercial adsorbents. It was found that both the precursor and activation methodology influence the adsorbents characteristics. Regarding nitrate uptake, their chemical surface was very relevant, while the textural properties did not exert a remarkable effect. Also, nitrate adsorption under acid pH was improved, especially for basic adsorbents, in contrast with neutral conditions, in which case no adsorbent stood out. The amelioration of nitrate removal for basic adsorbents and acidic pH conditions was associated to a greater prominence of electrostatic contributionsas well as a lower extent of adsorption competition between hydroxyl and nitrate ions.